2020
DOI: 10.1002/cche.10275
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on efficiency of nutmeg microencapsulation (freeze‐drying method) using native and OSA sorghum starch as wall materials in combination with gum arabic

Abstract: Background and objectives Nutmeg oleoresin (Myristica fragrans Houtt.) is used widely in the culinary, medicine, and ornamental products and is known for significant antioxidant, antifungal, antimicrobial, and pharmacological properties. Quality of nutmeg oleoresin can be retained through encapsulation techniques which suppresses the degradation of flavoring ingredients. The main objective of this research was to estimate the suitability and feasibility of sorghum starch (native and octenyl succinic anhydride)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The range of the average size of microcapsules obtained was between 21.07 ± 2.71 and 48.19 ± 2.33 μm (Mansour et al, 2020). A different study reported that freeze‐drying nutmeg oleoresin with two wall materials, sorghum starch and gum arabic, in the ratio of 1:2 resulted in the highest encapsulation efficiency and oil retention of 92.87% and 99.4%, respectively (Arshad et al, 2020). Miang is a fermented tea leaf that originated in northern parts of Thailand.…”
Section: Literature Review On the Encapsulation Of Bioactive Compound...mentioning
confidence: 99%
“…The range of the average size of microcapsules obtained was between 21.07 ± 2.71 and 48.19 ± 2.33 μm (Mansour et al, 2020). A different study reported that freeze‐drying nutmeg oleoresin with two wall materials, sorghum starch and gum arabic, in the ratio of 1:2 resulted in the highest encapsulation efficiency and oil retention of 92.87% and 99.4%, respectively (Arshad et al, 2020). Miang is a fermented tea leaf that originated in northern parts of Thailand.…”
Section: Literature Review On the Encapsulation Of Bioactive Compound...mentioning
confidence: 99%
“…Solubility (SY) was evaluated based on the method published by Arshad et al. (2020). The 10 mg/ml GM solution was stirred continuously for 30 min under room temperature and then centrifuged (3500 × g , 5 min).…”
Section: Methodsmentioning
confidence: 99%
“…The properties of the coating substance and the oleoresins significantly affect the efficiency of the process, storage stability, yield, and the controlled release of oleoresin. These interactions improved the retention and targeted delivery of these compounds (Arshad et al, 2020) [8] .…”
Section: Core Materialsmentioning
confidence: 99%